1999
DOI: 10.1073/pnas.96.20.11111
|View full text |Cite
|
Sign up to set email alerts
|

Tissue concentration of heparin, not administered dose, correlates with the biological response of injured arteries in vivo

Abstract: Drug activity is often studied in well controlled and characterized cellular environments in vitro. However, the biology of cells in culture is only a part of the tissue behavior in vivo. Quantitative studies of the dose response to drugs in vivo have been limited by the inability to reliably determine or predict the concentrations achieved in tissues. We developed a method to study the dose response of injured arteries to exogenous heparin in vivo by providing steady and predictable arterial levels of drug. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…In this study, the amounts of heparin that effectively increased survival of H. pylori are in the range available in vivo, as reported by Lovich & Edelman (1999), who concluded that approximately 0 . 3 mg ml À1 is found in arteries.…”
Section: Resultssupporting
confidence: 55%
“…In this study, the amounts of heparin that effectively increased survival of H. pylori are in the range available in vivo, as reported by Lovich & Edelman (1999), who concluded that approximately 0 . 3 mg ml À1 is found in arteries.…”
Section: Resultssupporting
confidence: 55%
“…Both heparin [31] and aspirin [32] can provide an anti-proliferative effect in addition to their anti-thrombotic effect. However, suppression of neointimal formation following experimental vascular injury requires substantially higher doses and far longer durations of administration (of heparin) than applied here [32][33][34][35]. The decrease in intimal hyperplasia with increased CRP though contrary to expectations may not be surprising in retrospect.…”
Section: Discussionmentioning
confidence: 67%
“…The need for a microscopic appreciation of the forces of drug distribution and transport is substantiated by recent studies that directly correlate local concentrations of therapeutic agents with ensuing biological response. 19,20 Although it is clear that absolute concentrations can determine biological effect, gradients in concentrations may also affect biological behavior. For instance, morphogens direct tissue formation in embryos by specifying cell fates along a concentration profile, 21,22 whereas the graded distribution of cytokines leads to the directed recruitment of inflammatory cells to sites of injury, minimizing their activities elsewhere.…”
Section: Continuum Pharmacokineticsmentioning
confidence: 99%